Acceptability of selected indigenous snacks by tourists in tourist centres in South Western, Nigeria (2018)
Indigenous snacks are powerful tool in promising great memories for tourists. Tourists hardly patronise them due to packaging. Attractive packaging could boost patronage of IS by tourists. Acceptability of indigenous snacks by tourists in Southwestern . Nigeria was conducted. The study was carried in southwestern states Nigeria, with peculiarity of selected IS. (Kokoro, Dodo Ikire, Akara Ogbomoso and Aadun) to the source of origin. Two tourists' centers frequently visited were purposively selected in each sampled state. Twenty tourists in each of the tourist centers were randomly selected given a sample size of 180 respondents. Tourists' age were 24.3±5.01 years. About half tourists were male (51.3%) and female (54.4%), had tertiary education (71.9%) and were single (51.3%) Most of the tourists (74.9%) earned less than?100,000.00±1,232.13per month. Majority (93.1%) of tourists had high knowledge of1$ and more than half (63.1%) had favourable attitudes to IS. Among tourists, Aadun had highest flavour (61.3%), taste (45.6%) and overall acceptability (68.8%>), while Akara Ogbomoso had the least flavour (41.3%), taste(22.5%>) and overall acceptability (49.4%). Tourists' attitude to IS was significantly higher in Oyo (107.18A9.0l), than Ogun (104.33±15.15), Osun (106.10±l5.20) and Ekiti (96.25±4.20). In order of magnitude of level of acceptability of IS, Ekiti (106.50±5.57) was highest compared to Osun (102.50±12.30), Oyo (92.85±15.67) and Ogun (85.80±l5.37). Age and educational level significantly influenced acceptability of IS by tourists, Knowledge (a = 0,184) attitude (a=0.06) and perception (a = -0.304) contributed significantly to acceptability of IS by tourists. Tourists’ acceptability level of repackaged indigenous snacks was high in Southwestern Nigeria. Determinants of tourists' acceptability of repackaged indigenous snacks were knowledge, attitude and perception.